Propuesta teórica de un Sistema de Alerta Temprana ante deslizamientos en la ciudad de Riobamba. - Buñay Zumba, Adriana Lorena (2023)
Landslides can have severe consequences, such as infrastructure damage, loss of human lives, property destruction, and alterations to the natural environment. Therefore, it is imperative to engage in land use planning and implement mitigation measures to reduce the risk of landslides, particularly in areas prone to such events. Furthermore, it is essential to pay heed to warnings issued by authorities and take precautions to safeguard both life and property in the event of a landslide. In order to conduct this study, it was necessary to identify landslide-prone areas and evaluate the risk associated with physical vulnerability. To determine the study area, a field investigation was conducted to gather the necessary information for assessing various parameters. The results obtained after a qualitative analysis in multiple areas indicated that the highest level of risk is located in the stretch from Los Shirys to Ciudadela Monseñor Leónidas Proaño neighborhoods, with a value of RVF of 28.24. This is the location where the SAT is intended to be implemented. For the theoretical proposal of SAT for landslides in the city of Riobamba, a comparison was made between community-based SAT and technological SAT, resulting in a hybrid SAT. This system will utilize an Arduino MEGA and sensors, including Fc28 humidity sensors, DHT11 sensors for temperature and relative humidity, and a tipping bucket rain gauge. These components, in combination with other devices, will provide an efficient and cost-effective SAT.